Kajian Analisis Pemberian Makanan Tambahan Berbahan Lokal: Percepatan Penurunan Stunting di Provinsi Sulawesi Tenggara Tahun 2023 - Banudi, La; Akbar Toruntju, Sultan; Koro, Suriana; Leksono, Purnomo; Usnia, Usnia (Poltekkes Kemenkes Kendari, 2024)
Background: Providing additional food made from local food is one strategy for handling nutritional problems in malnourished toddlers and SEZ pregnant women. In order to support improving the quality of Indonesian people, strengthening an economic structure that is productive, independent and competitive, the government has targeted an acceleration in reducing the stunting rate under five. In order to support the implementation of the Acceleration of Stunting Reduction which aims to achieve the quality development target by 2030 and the stunting prevalence target of 14% by 2024.Objective: To produce a comprehensive, up to date and effective analysis of supplementary feeding analysis: Accelerating Stunting ReductionResearch Method: This research uses a qualitative approach and design. Participants in this research were leaders and staff of institutions related to stunting prevention, namely: Provincial Health Services, District Services, Community Health Center Nutrition Officers and Posyandu Cadres. Materials and Tools: Questionnaire form, Camera, Video/handycam equipment, other ATK. This research was carried out in the Southeast Sulawesi Provincial Health Service Area, in June-November 2023. Data analysis method: Reading/studying the data, marking key words and ideas that is in the data. The steps in data analysis are data reduction, data presentation and conclusion drawing as follows: Data reduction, data presentation, conclusion drawingResults. PMT activities made from local food can build family independence in providing quality food for pregnant women and toddlers. Malnutrition among toddlers and pregnant women in KEK in Southeast Sulawesi. This problem must be corrected. One program is providing additional local food. Where Southeast Sulawesi is a coastal and island area that has a lot of food. The success of the local feeding program is demonstrated by improvements in the nutritional status of both targets. In toddlers, success can be seen from the weight gain each month. In this activity, the community health center plays a very important role. At the Puskesmas, all activities carried out by cadres can be monitored by the Puskesmas nutrition staff.Suggestion: Improvements in funding are needed, namely additional funds for food distribution to cadres, adequate transportation is needed. It is necessary to evaluate the process of providing additional food made from local ingredients and evaluate weight gain in children under five and increase in LILA size in pregnant women.